Reprogramming tumor-associated macrophages in gastric cancer: a pathway to enhanced immunotherapy - He, Yibo; Hong, Qianran; Chen, Shiliang; Zhou, Jiayi; Qiu, Shengliang (Frontiers in Immunology, 2025)
Gastric cancer (GC) remains a significant global health concern due to its poor prognosis and limited therapeutic options, particularly in advanced stages. Tumor microenvironment (TME), particularly tumor-associated macrophages (TAMs), plays a key role in tumor progression, immune evasion, and therapy resistance. TAMs exhibit plasticity, shifting between pro-inflammatory M1 and immunosuppressive M2 phenotypes, with the latter predominating in GC and contributing to poor outcomes. Recent therapeutic advancements focus on targeting TAMs, including inhibiting M2 polarization, reprogramming TAMs to M1 phenotypes, and combining TAM-targeted approaches with immune checkpoint inhibitors. Innovations in nanotechnology, metabolic reprogramming, and targeting key pathways such as interleukin-6 and C-C motif ligand 2/C-C motif chemokine receptor 2 further enhance these strategies. However, challenges remain, including the spatial and functional heterogeneity of TAMs within the TME and the need for selective targeting to avoid disrupting immune homeostasis. Ongoing research on TAM origins, functions, and interactions within the TME is crucial for developing precise and effective therapies. These advances hold promise not only for improving outcomes in GC but also for addressing other cancers with similarly complex microenvironments.